The Influence of CAR, NPL, LDR and DPK Ratios on ROE at Rural Credit Banks (BPR) in West Java - Riyadi, Dadan Slamet; Riyanti, Riyanti; Lukman, Lukman (Dinasti Publisher, 2025)
The objectives of this research are: 1) To determine and analyze the effect of the CAR ratio on ROE. 2) To find out and analyze the effect of the bad credit ratio (NPL) on ROE. 3) To find out and analyze the influence of the Loan Deposit Ratio (LDR) on ROE. 4) To determine and analyze the influence of Third Party Funds on ROE. 5) To determine and analyze the influence of the CAR Capital Adequacy Ratio, NPL, LDR and DPK together on ROE. This research uses a quantitative approach method. The total population of BPRs in the West Java region is 224 (two hundred and twenty four) Rural Banks (BPR). The sampling technique in this research is purposive sampling. The sample was 13 Rural Banks in the West Java region. Multiple linear regression method and to make the calculation easier, this research uses the Eviews 12 tool. The results of this research are that CAR has a positive and significant effect on the ROE variable. NPL has a negative and significant effect on the ROE variable. LDR has a negative and significant effect on the ROE variable. DPK has a positive and significant effect on the ROE variable. CAR, NPL, LDR and DPK simultaneously influence ROE